Macrophages Are Dispensable for Postnatal Pruning of the Cochlear Ribbon Synapses - Yu, Chaorong; Gao, Hui-Ming; Wan, Guoqiang (Frontiers in Cellular Neuroscience, 2021)
Ribbon synapses of cochlear hair cells undergo pruning and maturation before the hearing onset. In the central nervous system (CNS), synaptic pruning was mediated by microglia, the brain-resident macrophages, via activation of the complement system. Whether a similar mechanism regulates ribbon synapse pruning is currently unknown. In this study, we report that the densities of cochlear macrophages surrounding hair cells were highest at around P8, corresponding well to the completion of ribbon synaptic pruning by P8–P9. Surprisingly, using multiple genetic mouse models, we found that postnatal pruning of the ribbon synapses and auditory functions were unaffected by the knockout of the complement receptor 3 (CR3) or by ablations of macrophages expressing either LysM or Cx3cr1. Our results suggest that unlike microglia in the CNS, macrophages in the cochlea do not mediate pruning of the cochlear ribbon synapses.